2022
DOI: 10.1021/acscatal.2c05206
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Ortho C–H Arylation of Unprotected Anilines: Chemo- and Regioselectivity Enabled by the Cooperating Ligand [2,2′-Bipyridin]-6(1H)-one

Abstract: Metal-catalyzed C−H functionalizations on the aryl ring of anilines usually need cumbersome N-protection−deprotection strategies to ensure chemoselectivity. We describe here the Pd-catalyzed direct C−H arylation of unprotected anilines with no competition of the N-arylation product. The ligand [2,2′-bipyridin]-6(1H)-one drives the chemoselectivity by kinetic differentiation in the product-forming step, while playing a cooperating role in the C−H cleavage step. The latter is favored in an anionic intermediate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…This strategy has proved useful in our former studies on the role of cooperating bipyridone ligands in C–H activation. 19 The presence of a fluorinated tag is also very useful in the characterization of the species formed. Pyridine, a ligand of moderate coordination ability, completes the coordination sphere of palladium and imparts enough stability to the complexes without blocking further reactivity by ligand substitution.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy has proved useful in our former studies on the role of cooperating bipyridone ligands in C–H activation. 19 The presence of a fluorinated tag is also very useful in the characterization of the species formed. Pyridine, a ligand of moderate coordination ability, completes the coordination sphere of palladium and imparts enough stability to the complexes without blocking further reactivity by ligand substitution.…”
Section: Resultsmentioning
confidence: 99%
“…The Albéniz group recently managed to develop the direct ortho-arylation of primary and secondary anilines by means of palladium catalysis (Scheme 14). 32 The authors identified a This article is protected by copyright. All rights reserved.…”
Section: Direct C(sp 2 )-H Ortho-arylation Of Anilines With Arx (Orga...mentioning
confidence: 99%
“…The Albéniz group recently managed to develop the direct ortho -arylation of primary and secondary anilines by means of palladium catalysis (Scheme 14 ). 32 The authors identified a specific [(2,2′-bipyridin]-6(1 H )-one ligand as a crucial feature to obtain good regioselectivities in favor of the ortho position, as well as excellent chemoselectivities by circumventing the competitive Buchwald–Hartwig N -arylation reaction, most likely to happen in the case of N–H-containing anilines. This process proved efficient with primary and secondary anilines, however, a loss of regioselectivity was observed with N , N -dialkylated anilines.…”
Section: Ortho -Arylation Of Anilinesmentioning
confidence: 99%
“…There are a plethora of reports on achieving functionalization at the ortho-position of anilines via electrophilic and auxiliary assisted ortho-C-H activation. [38][39][40][41][42][43][44][45][46] On the other hand, it is important to note that meta-C-H functionalization is challenging and limited [47][48][49][50] due to the intrinsic electron donating nature of nitrogen in aniline systems. In this context, as far as we are aware, only three reports are known towards the meta-C-H alkenylation of anilines: namely, Yu's lab has disclosed the meta-C-H activation of anilines with the aid of a terminalnitrile containing directing template via an amide linkage 51 and later, Li et al, in 2017, revealed the meta-C-H functionalization of anilines by employing a carbamate-based linkage with the assistance of another aromatic-nitrile based directing template (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%